Analisis Perlindungan Data Pribadi Nasabah Perbankan Terhadap Penggunaan Layanan Mobile Banking - Fitriani, Sheila Aida; Sasra, Adelia Dara; Raharjo, Mohammad Harjuno Asmoro (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Security Of Mobile Banking Is A Concern For Bank Customers Who Use It, Even Though It Can Make Transactions Easier. To Protect Customers From Data Theft, Hacking And Exploitation For Illegal Purposes, Protecting Consumer Data Is Essential. The Author Wants To Investigate How Banking Customers' Personal Information Is Protected When Using Mobile Banking Services, Which Includes Banking Procedures In Protecting Customers' Personal Data Against Mobile Banking Use And The Implementation Of Regulations In Protecting Customers' Personal Data Against Mobile Banking Use In Indonesia. The Personal Data Protection (PDP) Law, Which Provides A Comprehensive Set Of Guidelines For The Processing Of Personal Data In All Sectors, Including Banking. This Research Aims To Examine Laws And Regulations In Indonesia Relating To The Protection Of Personal Information. In This Research, We Used A Normative Study Method Combined With A Conceptual Approach. By Using This Method, Researchers Can Find Out That Collaboration Between The Government, Regulators, Banks And The Community Is The Key To Creating A Safe And Trustworthy Mobile Banking Ecosystem. The Government And Regulators, Such As The Financial Services Authority (OJK) And Bank Indonesia (BI), Need To Continue To Update Regulations To Keep Pace With Technological Developments And Increasingly Complex Cyber Threats.